Synthesis and Modulation of Low-Dimensional Transition Metal Chalcogenide Materials via Atomic Substitution - Wang, Xuan; Chen, Akang; Wu, XinLei; Zhang, Jiatao; Dong, Jichen; Zhang, Leining (Nano-Micro Letters, 2024)
In recent years, low-dimensional transition metal chalcogenide (TMC) materials have garnered growing research attention due to their superior electronic, optical, and catalytic properties compared to their bulk counterparts. The controllable synthesis and manipulation of these materials are crucial for tailoring their properties and unlocking their full potential in various applications. In this context, the atomic substitution method has emerged as a favorable approach. It involves the replacement of specific atoms within TMC structures with other elements and possesses the capability to regulate the compositions finely, crystal structures, and inherent properties of the resulting materials. In this review, we present a comprehensive overview on various strategies of atomic substitution employed in the synthesis of zero-dimensional, one-dimensional and two-dimensional TMC materials. The effects of substituting elements, substitution ratios, and substitution positions on the structures and morphologies of resulting material are discussed. The enhanced electrocatalytic performance and photovoltaic properties of the obtained materials are also provided, emphasizing the role of atomic substitution in achieving these advancements. Finally, challenges and future prospects in the field of atomic substitution for fabricating low-dimensional TMC materials are summarized. Highlights: 1 Atomic substitution applied in the synthesis of different dimensional transition metal chalcogenide (TMC) is dissertated. 2 The controllable synthesis and property modification realization with atomic substitution or ion exchange are introduced. 3 The substitution principle and mechanism in different TMCs are concluded.